Quality of follow-up of preterm infants in the Primary Health Care network: "Qualipreterm" guide - Rosane Meire Munhak da Silva; Débora Falleiros de Mello (Associação Brasileira de Enfermagem, 2022)
ABSTRACT Objectives: to develop the first version of an assessment guide for the quality of follow-up of preterm infants in Primary Health Care. Methods: a descriptive methodological study, which developed a guide to assess follow-up quality of preterm infants in Primary Care. Steps of conceptual establishment, construction of items and answers, organization of domains and structuring of the guide were carried out. Results: the guide was organized in five domains that included: Hospital discharge planning and care plan organization; Home follow-up during visits and teleservice; Infant health monitoring to promote health and prevent injuries; Integration between health services, education and specialized monitoring; Family support and support for care. It is proposed to assess the domains in inadequate, regular, good and excellent. Final Considerations: the first version of the guide suggests assessment elements aimed at the recommendations of good practices for preterm infants' health in the Primary Health Care network.